Genetic determinants of haloarchaeal secondary metabolites, with focus on terpenes - Serrano, Susana Margarida Guerra (2023)
The knowledge on the secondary metabolites (SMs) produced by archaea is a field where few research and experimental testing ha s been done, when comparing to bacteria or fungi.The class Halobacteria, composed by haloarchaea that need high concentrations of salt to survive, has been one of the best well studied in the domain Archae a, in this regard. Some examples include the class model organisms Haloferax mediterranei, Haloferax volcanii and Halobacterium salinarum. Haloarchaea produce halocins that are peptides with anti-archaeal activity, but information regarding their biosynthesis and structure is still limited. Genes involved in the production of other peptides with post-translational modifications (RiPPs) have also been identifie d but, so far, none have been isolated or characterized. It is also known that the main carotenoid produced by haloarch aea is bacterioruberin, which has higher antioxidant capacity than β-carotene. Haloarchaea can also produce β-carotene (mainly as a precursor molecule) and canthaxanthin. The objectives of this study were: i) to characterize the diversity of SMs encoded in haloarchaeal genomes, in particular the diversity of genes involved in the production of carotenoids and ii) to evaluate the antibacterial activity of H. mediterranei ATCC 33500 and the impact of the production of bacterioruberin on its antimicrobial activity. Herein, 67 complete genomes of haloarchaea were analysed and 182 biosynthetic gene clusters (BGC) where 49% of them shared no homology. The BGCs identified encode the production of terpenes (70%), RiPPs (16%) and siderophores (14%). A closer inspection of the terpene BGCs allowed their division into two groups: those encoding a bifunctional protein lycopene cyclase/phytoene synthase gene (crtB, 53%) and those encoding a squalene synthase (sqs, 46.5%). The crtB gene was mostly found associated with the biosynthetic genes of bacterioruberin. However, in 22% of the strains, genes from retinal biosynthesis or genes not related with the production of carotene s were found in the proximity of crtB. The results obtained confirmed that all haloarchaeal strains should be able to produce bacterio ruberin. In addition , about 64% of the species may produce β -carotene as a precursor of retinal biosynthesis and 3% as a final product and/or precursor of canthaxanthin synthesis. A gene that putatively encodes a β - carotene ketolase (CrtO) was identified in Haloterrigena turkmenica. To date, these enzymes have not been characterized in haloarch aea, but may be involved in the biosynthesis of cant haxanthin . The crtB gene was associated to the bacterioruberin synthesis pathway through the generation of a kn ock -out mutant and carotenoid quantification. In addition to its anti -archaeal activity , it was determined that H. mediterranei is also able to inhibit the growth of Bacillus cereus. Finally, the H. mediterranei mutants lacking the crtB or sqs genes revealed the same antimicrobial profile as the wildtype strain. Thus, it was concluded that this bioactivity is not influenced by the production of bacterioruberin nor squalenes